Mandatory Disclosure and Medical Paternalism - Bullock, Emma C. (Ethical theory and moral practice, 2016)
Medical practitioners are duty-bound to tell their patients the truth about their medical conditions, along with the risks and benefits of proposed treatments. Some patients, however, would rather not receive medical information. A recent response to this tension has been to argue that that the disclosure of medical information is not optional. As such, patients do not have permission to refuse medical information. In this paper I argue that, depending on the context, the disclosure of medical information can undermine the patients ability to exercise her autonomy or have therapeutically detrimental effects. In the light of these insights I go on to develop a context-sensitive approach to medical disclosure. The advantage of this account is that it addresses concerns on both sides of the debate; whilst it acknowledges that patients do not have an exercisable right not to know, it allows that in some cases medical information ought to be withheld.